Desenvolvimento de um embutido frescal a partir da carne de pescoço de peru marinada - Souza, Amanda Cristina de (2019)
By-products of poultry industry present high technological value, such as turkey neck, that can be submitted to damp salting and marination processes, adding value and enabling the consumption and development of new products based on turkey. Therefore, the objective of this work was to develop a fresh sausage with marinated turkey neck meat. The equipment for the damp salting was developed and validated where samples of turkey neck meat measuring 1.0 x 3.0 x 6.0 cm (thickness x width x length) were submitted to the damp salting process. Previously, salt and maltodextrin concentrations, besides the temperature ranges of the marination process were determinated. From the selected parameters, a central rotational composite design 22with 11 (eleven) trials was used for damp salting. The turkey neck meat in the flat plate format were submitted to the marination in ternary solution containing sodium chloride, water and maltodextrinfor 0, 20, 45, 70, 95, 120 min. The influence of the parameters on the gain of solids and loss / gain of water was performed through multiple regression and response surface methodology, besides the adjustment of the data through the Azuara model. The apparent diffusivity of two solutes in the meat varied between 1.28 x 10-9 m2/s and 5.75 x 10-9 m2/s. In parallel, moisture, ash content, color and water activity were evaluated throughout the process (0, 20, 45, 70, 95 and 120 minutes), the pH and the firmness of the meat at the beginning and at the end of the damp salty. The use of higher concentrations of sodium chloride promoted higher solids gains and water loss for marinated turkey neck meat. The reduction of the pH and the water activity of the meat during the salting was due to the solutes incorporated in the process. The increase in ash content of the meat was proportional to the salt content incorporated over the course of the treatment period. There was a slight browning of the meat, demonstrated by the reduction of the parameters L*, a* and b*.The final moisture of the turkey neck was found within the limits established by the Brazilian Law. Then, three sausage formulations were prepared: 100% turkey neck meat (formulation 1), 100% pork swine (formulation 2 - control) and 50% turkey neck and 50% pork swine (formulation 3). The sausages were submitted to physical-chemical and sensorial analyzes. The elaborated formulations did not show significant changes in moisture, ash, water activity, parameter L* and b*. Therefore, the formulations showed significant alteration in pH, cooking water loss, firmness and a* parameter. Formulations 1 and 3 were well accepted, and for the intent-to-purchase analysis, 35.7% of the testers would purchase Formulation 1 and 42.8% of the testers would purchase Formulation 3. In the control difference test, there was significant difference (p<0,05) between the control sample and formulation 1 and 3. It was concluded that damp salting is an alternative in the use of turkey neck cuts, and can be used to add value to different by-products of the food industry.